2022
DOI: 10.1186/s13104-022-06220-y
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Japanese movement imagery questionnaire-revised second version

Abstract: Objective Developing a Japanese version of the Movement Imagery Questionnaire-Revised Second Version (MIQ-RS) is essential for widespread evaluation and treatment based on motor imagery in physically disabled persons and patients in rehabilitation. This study aimed to investigate the reliability and validity of the Movement Imagery Questionnaire-Revised Second Version (MIQ-RS), which assesses motor imagery ability, by translating it into Japanese. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…MI comprises two modalities, namely kinesthetic imagery and visual imagery. Moreover, the characteristics of MI vary among individuals [ 57 , 58 , 59 ]. Kinesthetic and visual modalities exhibit different EEG [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…MI comprises two modalities, namely kinesthetic imagery and visual imagery. Moreover, the characteristics of MI vary among individuals [ 57 , 58 , 59 ]. Kinesthetic and visual modalities exhibit different EEG [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Motor imagery is a cognitive process of imagining what it is like to exercise without actual movement [26]. Motor imagery can be divided into myosensory first-person imagery and visual third-person imagery, and previous studies have reported individual differences in motor imagery ability [27,28]. Motor imagery is known to improve performance [29] and has a motor-learning effect [30] even when the participant does not actually exercise.…”
Section: Motor Imagery-based Neurofeedbackmentioning
confidence: 99%